Torque oscillation characteristics in the process of bobbin tool friction stir welding - Shujin Chen (Journal of Vibroengineering, 2016)
This study analyzes torque oscillation characteristics in the process of bobbin tool friction stir welding. The empiral data of torque, the point temperature of contact surface and the leading point temperature is presented to explore the torque signal spectrum characteristics, the causes of the periodic oscillation of torque, the relationship between the oscillation and the surface forming of weld joint. The result shows that the torque in BTFSW has regular oscillation. The oscillation frequency of the torque is nearly 2 times the spindle frequency. With the increase of rotary speed, the oscillation frequency and the frequency difference increase gradually. There is no significant linear relationship between the amplitude peak of the torque, traveling speed, rotary speed and the measured point temperature. The instable temperature of the leading areas to be welded inevitably leads to the instability of the torque amplitude. The analysis indicates that the more intense of the heat input rate, the more obvious of the torque vibration, and the small and uniform torque amplitude does not affect the surface shape. Once the oscillation is abnormal, it easily leads to the poor surface forming and the hole defect.